Pendampingan Penggunaan Layanan Perbankan Digital Pada Nasabah BANK BPD Bali Capem PUSPEM BADUNG - Lestari, Ni Komang Ayu Srigita; Putri, Putu Indah Dianti (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Abstract Assistance with Digital Banking Services Usage at Bank BPD Bali Capem Puspem Badung identifies low levels of digital technology adoption among customers as a major challenge. Despite Bank BPD Bali’s commitment to regional economic development and providing inclusive banking services, many customers still rely on cash transactions and physical visits to the branch. This Internship Program aims to enhance understanding and usage of digital banking applications through intensive support. This approach includes direct education on how to use the app, its benefits, and technical problem- solving. Results show an improvement in customers' understanding and skills in using digital services, but challenges related to digital literacy still need to be addressed. The program demonstrates effectiveness in increasing digital service adoption, supporting Bank BPD Bali’s goal of delivering more efficient and high-quality banking services, and contributing to the economic development of Bali. Evaluation and the development of a structured monitoring system are necessary to ensure the program’s sustainability and effectiveness in the future. Kata Kunci: digital banking, customer assistance, digital literacy, technology adoption